Domain science and engineering from computer science to the sciences of informatics. Part II: Science - Bjorner, D. (Кибернетика и системный анализ, 2011)
We discuss means for describing domains. We do so on the background of the example of part I of the present (Part II) paper and in its discussion. The discussion amounts to a proposal for a base description ontology. The discussion borders between computer science and an emerging Philosophy of Informatics. As such it is very tentative. The present discussion might inspire better minds to put this border area on a stronger footing. Проаналізовано засоби опису предметних областей на прикладі із ч. I даної статті. Мета аналізу — утворення онтології базового опису. Обговорення ведеться на межі комп’ютерних наук і філософії інформатики — галузі, що перебуває на стадії становлення. Публікація сприятиме утвердженню даної предметної області.